Book Reviews (Historia, 2021)
1. Cabo deel I2. I . H . Enklaar: Levensgeschiedenis van J . T . van der Kemp 3. H . M . Rex: Nederduitsch Hervormde Gemeente Bronkhorstspruit 4. J . P . Lynch: Aristotle's School 5. P . J . W . Beltjes: Culemborgers Overzee6. G . H . Findlay: Dr . Robert Broom7. G . Brown: An Artist's Journey along the old Cape Post Road8. R . F . Kennedy: Catalogue of Pictures in the Africana Museum 9. J . D . Gould: Economic Growth in History10. A . G . Oberholster: Dagboek van H . C . Bredell 11. Hans Sauer: Ex Africa12. F . C . Selous: Travel and Adventure in South East Africa13. E . Mohr: To the Victoria Falls14. A . Sillery: John Mackenzie of Bechuana 15. V . Allen: Kruger's Pretoria16. E . K. Lorimer: Panorama of Port Elizabeth